Avaliação da relação da densidade de vetores e da presença de Aedes aegypti infectados com a ocorrência de dengue na cidade de Vitória - Piccin, Mariela Pires Cabral (2013)
Dengue is an acute febrile disease caused by dengue virus (DENV), which groups four serotypes. It is transmitted by the bite of female mosquitoes of the gender Aedes, being the Aedes aegypti the principal vector with epidemiologic importance. Vector control and epimiological surveillance are the principal tools for epidemic’s contention. So, the objective of this study was to observe the relationship between vector density or infection of the vectors by DENV with the cases of dengue in Vitória. Confirmed and notified cases on SINAN and data from the programme MI –Dengue were analised. For the identification of virus serotypes, it was made RT-PCR. Also, it was described the spatial distribution of human cases of dengue, as well the spatial distribution of vector’s density and the traps where infected mosquitoes were found. As a result, it was found a small predominance of women in the sample analised (54,27%) and 64,18% of the cases occurred in people with more than 18 years old. 90,74% were classified as dengue fever, while 6,60% were classified as “dengue with complications” and 2,66% as “dengue haemorrhagic fever”. In 8,23% of the cases, there was the necessity of hospitalization and 2 deaths were contabilized during the period. Trough the temporal analysis, it was observed that the increase in vector’s density occurred in the warm and rainy times, and it preceeded the increase in human cases. During all the year of 2011, A. aegypti’s density in the city was considered as “moderate” or “critical”. It was not observed a correlation between vector’s density and incidence of dengue in the neighborhoods (p = 0.848), but the neighborhoods where it was found infected mosquitoes had greater incidence of dengue than the neighborhoods without infected vectors (0.009). By the RT-PCR assay, it was observed that the major serotype found in human samples and in vector samples was DENV-1 (96,56% e 82,35%, respectively). DENV-2 was also found in circulation, but in smaller rates.